World Oral and Maxillofacial Trauma (WORMAT) project: A multicenter prospective analysis of epidemiology and patterns of maxillofacial trauma around the world. - Roccia, Fabio; Iocca, Oreste; Sobrero, Federica; Rae, Euan; Laverick, Sean; Carlaw, Kirsten; Aquilina, Peter; Bojino, Alessandro; Romeo, Irene; Duran-Valles, Francesc; Bescos, Coro; Segura-Palleres, Ignasi; et al. (Elsevier, 2022)
Background/Aim: The World Oral Maxillofacial Trauma (WORMAT) project was performed to analyze the causes and characteristics of maxillofacial fractures managed in 14 maxillofacial surgery divisions over a 1-year period. Methods: The following data were collected: age, sex, cause and mechanism of maxillofacial fracture, alcohol and/or drug abuse at the time of trauma, fracture site, Facial Injury Severity Scale score (FISS), associated injury, day of trauma, timing and type of treatment, and length of hospitalization. Statistical analyses were performed using SPSS software. Results: Between 30 September 2019 and 4 October 2020, 2,387 patients (1,825 males and 562 females [ratio 3.2:1], 47.6% aged 20–39 years [mean age 37.2 years, median 33.0 years]) were hospitalised. The main cause of maxillofacial fracture was road traffic accidents (RTA), which were statistically associated with male adults as like as assault, sport, and work (p<0,05). Half of the fractures involved the middle third of the face, statistically associated with fall and assault (p<0.05). Trauma in multiple locations was significantly associated with longer hospital stay (p<0.05). The mean length of hospitalization was 3.9 days (95% Confidence Interval 3.7–4.2). Conclusions: This prospective, multicenter epidemiological study confirmed that young adult males were the ones most commonly affected by maxillofacial fracture. RTAs and assaults are statistically associated with the adult population, while falls are associated with females and older population.
Keywords: Epidemiology; Fracture; Maxillofacial; Multicenter; Prospective